Restoration of cellular immunity in HIV-infected individuals on antiretroviral therapy - Fatime Ramla, Tanko (Division of Virology, 2017)
During the course of HIV pathogenesis, the virus induces multiple defects in immune cells, altering their functional ability to efficiently control HIV itself and other infections. Whilst the widespread implementation of antiretroviral therapy (ART) has led to reduced morbidity and mortality in most HIV-infected individuals having access to treatment, we still do not know whether full restoration of immune function occurs. The aim of this study was to assess the extent to which ART restores both phenotypic and functional T and B cell immunity. HIV-infected women were studied before and 1 year after ART initiation. In Chapter 2, the effect of ART on T cell activation and differentiation profiles was evaluated in HIV-infected individuals (n=28; pre- and post-ART), and compared to HIVuninfected age- and sex-matched controls (n=23). In Chapter 3, the restoration of copathogen specific CD4+ T cells was determined by comparing their cytokine secretion ability and memory differentiation profiles in response to Mycobacterium tuberculosis and cytomegalovirus in HIV-infected (n=15; pre- and post-ART), compared to uninfected (n=9) individuals. Finally, Chapter 4 examined changes in B cell activation and memory profiles in HIV-infected persons (n=19; pre- and post- ART), and compared profiles to HIV-uninfected individuals (n=19). Multiparameter flow cytometry was performed to address the study objectives. T cell activation, as measured by CD38 and HLA-DR expression, was significantly reduced one year after ART for both CD4+ and CD8+ T cells, but normalisation to levels in HIV-uninfected individuals did not occur, despite suppression of viral load. In addition, skewed CD4+ and CD8+ T cell memory profiles were not completely restored. Furthermore, no change in the cytokine production capacity and memory profile of pathogen-specific CD4+ T cells was found before and after ART, but pathogen-specific CD4+ T cells exhibiting a late differentiated profile (CD27- CD45RO+) had a lower ability to replenish (p=0.02; r = -0.5) compared to cells with an early differentiated profile (CD27+CD45RO+; p=0.04; r = 0.45) prior to ART. Similar to T cells, activated B cells (CD40+CD86+) were only partially normalised post-ART, and remained significantly higher than B cells of HIV-uninfected individuals. The frequency of all B cell memory subsets were comparable between HIV-treated and uninfected individuals, with the exception of plasmablasts, whose frequency was still significantly higher than in HIV-uninfected subjects. In summary, these results demonstrate that HIV-infected women on suppressive ART show a substantial but only partial normalisation of T cell and B cell memory subsets, and lower levels of T cell and B cell activation. In addition, restoration of co-pathogen specific memory CD4+ T cells upon treatment was dependent on their memory profile before ART. Understanding the impact of HIV on T and B cell dysfunction and restoration upon ART may provide important insights into the mechanisms of HIV pathogenesis in the era of ART.